2012
DOI: 10.1063/1.4742198
|View full text |Cite
|
Sign up to set email alerts
|

1.3 μm InAs/GaAs quantum dot lasers on Si substrates by low-resistivity, Au-free metal-mediated wafer bonding

Abstract: Over 1.3 μ m continuous-wave laser emission from InGaSb quantum-dot laser diode fabricated on GaAs substrates Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Metal bonding techniques have also been used for the fabrication of hybrid III/V/Si lasers [231], [232]. In 2013, Skorpios Technologies reported the first III/V/SOI hybrid laser fabricated in a commercial foundry, based on the metal bonding of a III/V die onto SOI [233].…”
Section: I N T E G R At E D L I G H T S O U R C E Smentioning
confidence: 99%
“…Metal bonding techniques have also been used for the fabrication of hybrid III/V/Si lasers [231], [232]. In 2013, Skorpios Technologies reported the first III/V/SOI hybrid laser fabricated in a commercial foundry, based on the metal bonding of a III/V die onto SOI [233].…”
Section: I N T E G R At E D L I G H T S O U R C E Smentioning
confidence: 99%
“…However, the drawback of the AuGeNi-assisted bonding is the Au contamination. Thus, Tatsumi et al (2012) further demonstrated an Au-free metal-assisted wafer bonding for lasers on silicon chip. Besides, Creazzo et al (2013) also demonstrated another type of silicon laser by using metal-assisted bonding of III/V epitaxial material directly onto the silicon substrate.…”
Section: Review On Research For Lasers On Siliconmentioning
confidence: 99%
“…Besides these direct growth techniques, wafer bonding technologies have also been used to integrate high-performance InAs quantum dots lasers on silicon substrates. [14][15][16] The performance of such bonded InAs QD lasers is often degraded by the high temperature of the bonding process (>300 C for at least a few hours), [14][15][16][17][18][19][20][21][22] which intermixes the InAs QDs and their GaAs capping and spacer layers. On the other hand, it has been demonstrated that Palladium can form a solid alloy with III-V materials, such as Pd 4 GaAs or Pd x InP, by a solidphase topotaxial reaction at room temperature.…”
mentioning
confidence: 99%
“…It was found that permanent bonding can be achieved at a low temperature and time of 250 C and 1.5 h, respectively, at 1000 mbar pressure which is at least 50 C and 50% less than previously described metal-mediated bonding techniques. [14][15][16] After bonding, the GaAs substrate is removed by a combination of mechanical polishing and wet chemical etching, where the 30 nm Al 0.85 GaAs in the heterostructure acts as an etch stop layer. After removing the Al 0.85 GaAs, the ridge waveguide lasers are fabricated by standard process where the waveguide width of 5 lm was fixed and the cavity lengths were varied from 1000 to 2000 lm, respectively.…”
mentioning
confidence: 99%